The Relationship between Health Workers’ Motivation and Support and Pregnant Women’s Adherence to Iron Supplements - Dinda Nabila Firmansyah; Susilawati Susilawati; Johan Budhiana (Indonesian Journal of Global Health Research, 2026)
Anemia in pregnancy is defined as a hemoglobin (Hb) level below normal thresholds and is commonly associated with inadequate intake of essential micronutrients, such as iron, folic acid, and vitamin B12, which are important for erythropoiesis. Poor adherence to iron and folic acid supplementation remains a major contributor to maternal anemia. Therefore, internal motivation and healthcare provider support are key factors in ensuring effective nutritional interventions during pregnancy. This study aimed to examine the association between internal motivation and healthcare provider support with adherence to iron supplementation among pregnant women in Karang Tengah, Sukabumi City, in 2026. A correlational study with a cross-sectional design was conducted involving 80 pregnant women selected through total sampling. Data were collected using structured questionnaires, while adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), which has demonstrated reliability Cronbach’s alpha = 0.796. Data were analyzed using the Somers’ d test. The results showed that most respondents had moderate motivation (55.0%), perceived healthcare provider support as inadequate (56.3%), and demonstrated low adherence (46.3%). Statistical analysis revealed significant associations between both variables and adherence (p = 0.001). In conclusion, both factors are significantly associated with adherence to iron supplementation among pregnant women.